Cover Image, Volume 53, Number 9, September 2018. Issue 9 (24th August 2018) - Strang, Abigail; Ryan, Lauren; Rahman, Tariq; Balasubramanian, Sona; Hossain, Jobayer; Heinle, Robert; Shaffer, Thomas H.
Abstract : The cover image, by Abigail Strang et al., is based on the Original Article: Pulmonary Physiology Measures of Respiratory Inductance Plethysmography (RIP) in Children with Neuromuscular Disease, DOI: 10.1002/ppul.24134 . Image Credit: Cindy Brodoway of Nemours duPont Children's Hospital. Funding Credit: The Nemours Foundation; The Univ. of Delaware, Center for Advanced Technology (CAT) Program Grant #44058 (TR & THS); and NIH COBRE, P30 GM114736 (THS).